2007
DOI: 10.1002/ptr.2097
|View full text |Cite
|
Sign up to set email alerts
|

Total phenolic contents, free radical scavenging activities and inhibitory effects on the activation of NF‐kappa B of eight Centaurea L. species

Abstract: Extracts obtained from aerial parts of eight Centaurea L. (Asteraceae) species (C. calolepis, C. cariensis subsp. maculiceps, C. cariensis subsp. microlepis, C. hierapolitana, C. cadmea, C. ensiformis, C. depressa and C. urvillei subsp. urvillei), were tested for their free radical scavenging activity (FRSA) in the DPPH screening assay, for their in vitro antiinflammatory activity in the reporter gene assay for inhibition of transcription factor NF-kappaB and for their total phenolic content. Methanol extracts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
27
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 11 publications
9
27
1
1
Order By: Relevance
“…urvillei. The highest yield was gained from methanol extracts (Karamenderes et al, 2007). This result is in agreement with that reported by Csupor-Loffler et al (2009).…”
Section: Discussionsupporting
confidence: 92%
“…urvillei. The highest yield was gained from methanol extracts (Karamenderes et al, 2007). This result is in agreement with that reported by Csupor-Loffler et al (2009).…”
Section: Discussionsupporting
confidence: 92%
“…In another study, the total phenolic content of C. urvillei subsp. urvillei was detected as 103.44 mgGAEs/g extract 27 . From the result, it can be concluded that C. urvillei subsp.…”
Section: Results and Discussion Total Bioactive Componentsmentioning
confidence: 99%
“…Several species from the genus Centaurea are interesting from medicinal and pharmacological perspective, and thus recently the subject of intensive research [3][4][5][6][7][8][9][10][11][12][13][14]. Since structural and phytochemical characteristics of C. sadleriana were previously unknown, our work highlights this information.…”
Section: Discussionmentioning
confidence: 98%
“…As Centaurea species were generally classified as essential oil-poor plants, the investigations of these and antioxidant properties are rather scarse. However, antiinflammatory, antimicrobial, antifungal and cytotoxic activities had been found for extracts or natural products of some of the Centaurea species [3,[5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%